Representation of Donald Trump in Metaphtonymic Internet Memes as an Instrument of Socio-Political Influence - Martynyuk , Alla; Nabokova , Iryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article focuses on the constitutive features of political internet memes representing the 47th President of the United States, Donald Trump. All the memes analysed are responses to Trump’s post on his own social media platform, Truth Social, in which he claimed that he would be the world’s best Pope. The relevance of the study is accounted for by the need to elucidate the principles of interaction between the verbal and visual modes in metaphtonymic internet memes in achieving socio-political communicative impact, as well as establishing the contribution of these modes and verbal allusion to the creation of a humorous effect as an instrument of communicative influence. The process of communication as part of socio-political processes has been analysed in terms of the methodology of multimodal cognitive linguistics. The internet meme is viewed as an interactive text, predominantly humorous in nature, circulating on the Internet as a historically established media resource providing the possibility of combining visual and verbal semiotic modes to achieve situationally determined communicative goals. The interpretation of an internet meme is possible only in the context of current socio-political events relevant for a particular society. The humorous effect of metaphtonymic memes stems from their structure containing at least two incompatible conceptual structures that are simultaneously activated in the recipient’s mind, followed by a two-stage model of resolving incongruity. The application of the cognitive metaphor and metonymy theory to multimodal communication analysis has made it possible to identify and describe visual metaphtonymy as well as visual-verbal metaphtonymy interacting with allusion. Both types of metaphtonymy are constructed on the basis of several metonymies, each activating conceptual structures of certain experiential domains, while metaphor establishes connections between these structures by projecting features from the source domain onto the target domain. The incompatibility of the activated conceptual structures creates a humorous stimulus and highlights the incongruity between Trump’s traits and the expectations of the global mass audience regarding the President of the United States. Thus, metaphtonymic memes exert socio-political influence on recipients and function as instruments for shaping public opinion.